Dental Students in Germany throughout the COVID-19 Pandemic: A Psychological Assessment and Cross-Sectional Survey - Mohamed Mekhemar (Biology, 2021)
Multiple investigations have reported high psychological distress among students since the coronavirus (COVID-19) outbreak started. This survey examined the associations between psychological features, and several demographic and social factors among dental students in German universities. Dental students registered in German universities nationwide were asked to join this survey via a self-directed online questionnaire, from July 2020 to January 2021. This study assembled data on demographic statistics, the depression anxiety stress scales (DASS-21), and the impact of events scale—revised (IES-R) instrument. The relationships between demographic-related variables and mental consequences of depression, anxiety, stress, intrusion, avoidance, and hyperarousal were inspected. Two hundred and eleven students contributed to the questionnaire and conveyed overall normal or mild outcomes of depression, anxiety, stress, intrusion, avoidance, and hyperarousal. In addition, female gender, cardiovascular diseases, smoking habits, and seeing the COVID-19 outbreak as a financial risk were stated as significant related factors (p < 0.05), with increased IES-R and DASS-21 scores. These results highlight the features that should be considered to better protect dental students’ mental health in German universities during the crisis.